2017
DOI: 10.1128/cvi.00186-16
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Immune Components of Anti-Diarrheagenic Enterotoxigenic Escherichia coli Hyperimmune Bovine Colostrum Products

Abstract: Diarrhea is a common illness among travelers to resource-limited countries, the most prevalent attributable agent being enterotoxigenic Escherichia coli (ETEC). At this time, there are no vaccines licensed specifically for the prevention of ETEC-induced traveler's diarrhea (TD), and this has propelled investigation of alternative preventive methods. Colostrum, the first milk expressed after birthing, is rich in immunoglobulins and innate immune components for protection of newborns against infectious agents. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…However, further experiments would be required to understand the exact mechanism why IMM-124E is most effective at 100mg/kg. A recent study that investigated how IMM-124E might exert its anti-diarrheagenic effects, demonstrated that IMM-124E has direct anti-bacterial activity via inhibition of growth and migration of bacteria 21 . This indicates that also during colitis, the beneficial effect of IMM-124E is possibly due to direct anti-bacterial properties, which might lead to decreased translocation of invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further experiments would be required to understand the exact mechanism why IMM-124E is most effective at 100mg/kg. A recent study that investigated how IMM-124E might exert its anti-diarrheagenic effects, demonstrated that IMM-124E has direct anti-bacterial activity via inhibition of growth and migration of bacteria 21 . This indicates that also during colitis, the beneficial effect of IMM-124E is possibly due to direct anti-bacterial properties, which might lead to decreased translocation of invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…IMM-124E is a bovine colostrum-based product obtained from cows that have been immunized with LPS from Escherichia coli, which results in high levels of LPS-specific IgG. A study investigating the composition of IMM-124E has been published recently, showing that 1mg IMM-124E powder contains about 0.4mg total IgG, which is comparable to the total IgG content in colostrum powder 21 . In previous studies, it has been demonstrated that administration of IMM-124E ameliorates disease in a model of non-alcoholic steatohepatitis (NASH) 22,23 , a disease where chronic presence of LPS and subsequent low-grade inflammation might promote disease activity 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, preventive methods to reduce the risk of ETEC-induced diarrhea have been proposed. A hyperimmune bovine colostrum (HBC) produced by immunization of cows during gestation has proven clinically effective in preventing ETEC diarrhea (Sears et al, 2017 ). Among non-antibiotic therapies, vaccine development is a strategy of choice but, to date, there is no universal or specific licensed vaccine against InPEC.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that colostrum-derived antibodies, due to their intrinsic nature, are able to survive the orogastric delivery route better, thereby providing more active antibody to the gut. 35 While not addressed in this study, it would be of value to determine the amount of functional antibody available in the gut following ingestion. Consistent with the data seen here, we previously observed a low number of anti-CS6 responders after oral challenge with CS6+ ETEC B7A strain (K. Talaat et al, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%